RETRACTED: Relating Sustainable Business Development Practices and Information Management in Promoting Digital Green Innovation: Evidence From China - Wen Huang; Ka Yin Chau; Ip Yun Kit; Naila Nureen; Muhammad Irfan; Muhammad Irfan; Muhammad Irfan; Azer Dilanchiev (Frontiers in Psychology)
Digital green innovations are being implemented in manufacturing to help organizations achieve sustainability by adopting sustainable development practices (SDPC). However, little is known about the impact of the information management process (IMP) on organizations’ digital green innovation. To address this gap, we devised a multidimensional framework based on the resource-based view (RBV) theory that serves as a basis for sculpting how the IMP captured and sustained organizational digital green innovation via SDPCs. 533 respondents from big and medium-sized manufacturing businesses in China were surveyed, and data were analyzed using the structural equation modeling (SEM) approach. The study makes numerous significant findings. Firstly, the SDPC’s dimensions (environment, economic, and social) are considerably improved by the IMP’ dimensions (acquisition, dissemination, and application). Secondly, SDPC’s dimensions are critical for attaining organizations’ digital green innovation. Thirdly, SDPCs’ implementation mediates the linkage between the IMP and organizations’ digital green innovation. Our findings suggest that investing in and implementing cutting-edge technology and sustainable practices are critical for long-term success. Still, soft issues, such as organizational information management, are equally critical in today’s information-based economy. Finally, in light of the study findings, we present theoretical and managerial implications.